Economics of chhari and marketable-size carps in Bara, Nepal - Adhikari, Prabin; Jha, Dilip Kumar; Poudel, Mousami; Gurung, Suraj; Acharya, Mahesh Chandra (Journal of Agriculture and Natural Resources, 2019)
A study was conducted to analyze the economics of production of chhari and marketable-size carps in Bara, Nepal. All total 90 farmers; 45 chhari producing and 45 marketable-size carps producing farmers were selected randomly and surveyed through pre-tested semi-structured interview based schedule on the month of March, 2019. Data was entered and analyzed using STATA 12.1 and SPSS 25. Findings of the study revealed that the total cost of fish production per hectare of pond area was 971927 NRs/year. Chhari production was profitable in the study area as compared to marketable-size carps with a Benefit Cost Ratio of 1.97 and 1.67 respectively. Production function analysis including six explanatory variables, showed significant effect of feed, labour (p